2017
DOI: 10.1161/jaha.116.005077
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Biomarkers Interleukin‐6 and C‐Reactive Protein and Outcomes in Stable Coronary Heart Disease: Experiences From the STABILITY (Stabilization of Atherosclerotic Plaque by Initiation of Darapladib Therapy) Trial

Abstract: BackgroundEvaluation of cardiovascular prognosis in patients with stable coronary heart disease is based on clinical characteristics and biomarkers indicating dysglycemia, dyslipidemia, renal dysfunction, and possibly cardiac dysfunction. Inflammation plays a key role in atherosclerosis, but the association between inflammatory biomarkers and clinical outcomes is less studied in this population.Methods and ResultsOverall, 15 828 patients with coronary heart disease in the STABILITY (Stabilization of Atheroscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
127
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(150 citation statements)
references
References 27 publications
(27 reference statements)
3
127
1
1
Order By: Relevance
“…Among patients with clinically manifest vascular disease, more than 20% showed a risk of recurrent events in the excess of 30% over 10 years, including MI, stroke, or vascular death, thus indicating an area of unmet medical need [2]. The persistence of high risk has been increasingly associated with elevated levels of proinflammatory molecules, such as cytokines and acute-phase reactants [3]. Indeed, beyond the well-known role of LDL in atherosclerosis, data from the proof-of-concept CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) trial [4] have clearly identified inflammation as one of the key biological processes of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with clinically manifest vascular disease, more than 20% showed a risk of recurrent events in the excess of 30% over 10 years, including MI, stroke, or vascular death, thus indicating an area of unmet medical need [2]. The persistence of high risk has been increasingly associated with elevated levels of proinflammatory molecules, such as cytokines and acute-phase reactants [3]. Indeed, beyond the well-known role of LDL in atherosclerosis, data from the proof-of-concept CANTOS (Canakinumab Anti-Inflammatory Thrombosis Outcome Study) trial [4] have clearly identified inflammation as one of the key biological processes of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…With a series of eligible compounds available at present, scientists would be admired if they exerted more effort in exploring the role of Lp‐PLA2 in diseases other than atherosclerosis, particularly, in microvascular diseases that may be more sensitive to Lp‐PLA2 inhibition. In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp‐PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib . To conclude, we anticipate that the story of Lp‐PLA2 will continue.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp-PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib. [279][280][281][282][283][284][285][286][287][288] To conclude, we anticipate that the story of Lp-PLA2 will continue.…”
mentioning
confidence: 98%
“…There is a strong association between inflammatory biomarkers and increased risk of metabolic and cardiovascular disorders (63)(64)(65). In the past few years, researchers interest was increased toward studying the effects of Ramadan diurnal IF on inflammatory biomarkers.…”
Section: Effects On Inflammatory Biomarkersmentioning
confidence: 99%